VD_FINDINFO HC / 2012 / 52 vom 7. Dezember 2011 - VD Tribunal cantonal (2011)
DÉNUEMENT, ASSISTANCE JUDICIAIRE | 117 CPC (CH), 118 CPC (CH), 119 al. 6 CPC (CH), 121 CPC (CH), 319 let. b ch. 1 CPC (CH)